Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/s21020624
|View full text |Cite
|
Sign up to set email alerts
|

Back-Gate GaN Nanowire-Based FET Device for Enhancing Gas Selectivity at Room Temperature

Abstract: In this work, a TiO2-coated GaN nanowire-based back-gate field-effect transistor (FET) device was designed and implemented to address the well-known cross-sensitive nature of metal oxides. Even though a two-terminal TiO2/GaN chemiresistor is highly sensitive to NO2, it suffers from lack of selectivity toward NO2 and SO2. Here, a Si back gate with C-AlGaN as the gate dielectric was demonstrated as a tunable parameter, which enhances discrimination of these cross-sensitive gases at room temperature (20 °C). Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Gas sensors based on field-effect transistors (FETs) have drawn much attention due to their capability to provide a multi-parameter response, such as the charge carrier mobility, on/off current ratio, threshold voltage, and bulk conductivity, for accurate interpretation. There are several types of FET gas sensors depending on the applied semiconductors: inorganic semiconductors, carbon materials, layered materials, organic semiconductors, and organic–inorganic hybrid materials. For instance, an FET based on metal oxide, which is regarded as one of the most traditional gas-sensing materials, can detect target gases by chemical interaction with the adsorbed oxygen ions in metal oxide . However, the operating temperature in the metal oxide sensor is relatively high, and thus, reducing the temperature to room temperature is a target goal. , On the other hand, two-dimensional (2D) materials such as graphene or MoS 2 can be used to fabricate room-temperature-operating gas sensors. , However, the operating principle typically depends on the charge transfer (CT) between active layers and physisorbed gas molecules. , For this reason, target gas molecules are limited to dipolar gases (i.e., NO 2 and NH 3 ), and the selectivity is generally low. Conjugated polymers (CPs) are desirable active layers for developing wearable gas sensors. , Although field-effect mobilities of CPs are relatively low, recently developed diketopyrrolopyrrole (DPP) polymers exhibiting high mobility could be an alternative for the highly sensitive FET-based gas sensors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas sensors based on field-effect transistors (FETs) have drawn much attention due to their capability to provide a multi-parameter response, such as the charge carrier mobility, on/off current ratio, threshold voltage, and bulk conductivity, for accurate interpretation. There are several types of FET gas sensors depending on the applied semiconductors: inorganic semiconductors, carbon materials, layered materials, organic semiconductors, and organic–inorganic hybrid materials. For instance, an FET based on metal oxide, which is regarded as one of the most traditional gas-sensing materials, can detect target gases by chemical interaction with the adsorbed oxygen ions in metal oxide . However, the operating temperature in the metal oxide sensor is relatively high, and thus, reducing the temperature to room temperature is a target goal. , On the other hand, two-dimensional (2D) materials such as graphene or MoS 2 can be used to fabricate room-temperature-operating gas sensors. , However, the operating principle typically depends on the charge transfer (CT) between active layers and physisorbed gas molecules. , For this reason, target gas molecules are limited to dipolar gases (i.e., NO 2 and NH 3 ), and the selectivity is generally low. Conjugated polymers (CPs) are desirable active layers for developing wearable gas sensors. , Although field-effect mobilities of CPs are relatively low, recently developed diketopyrrolopyrrole (DPP) polymers exhibiting high mobility could be an alternative for the highly sensitive FET-based gas sensors .…”
Section: Introductionmentioning
confidence: 99%
“…6,10 However, the operating principle typically depends on the charge transfer (CT) between active layers and physisorbed gas molecules. 11,12 For this reason, target gas molecules are limited to dipolar gases (i.e., NO 2 and NH 3 ), and the selectivity is generally low. Conjugated polymers (CPs) are desirable active layers for developing wearable gas sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, the energy gap acts as an energy barrier for gas absorption and electron transfer. That means controlling the gate bias causes the Fermi level of the metal oxide to be much closer to the conduction band, lowering the energy barrier and improving gas sensing performance as shown in Figures S4 C and S4D ( Henning et al., 2015 ; Khan et al., 2021 ). Highly doped Si with 300-nm-thick SiO 2 was adopted as a back gate to elucidate the effect of back-gate bias on the sensing characteristics at room temperature, as shown in Figure 3 A.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the vertical electric field accelerated the release of surface-trapped carriers by charge exchange between the TiO 2 sensing channel and alcohol molecules, resulting in a shift in the Fermi energy level. 9 A comparison of the alcohol sensing performances of different TFT sensors is tabulated in Table 1. Wongrat et al reported the ZnO nanostructure-based field effect transistor (FET) sensor for ethanol sensing at room temperature and compared it with the ZnO thin film FET sensor.…”
Section: Sensor Studymentioning
confidence: 99%